Achieving efficient nitrogen removal and nutrient recovery from wastewater in a combining simultaneous partial nitrification, anammox and denitrification (SNAD) process with a photobioreactor (PBR) for biomass production and generated dissolved oxygen (DO) recycling. (November 2018) - Zou, Yu; Xu, Xiaochen; Wang, Xiaojing; Yang, Fenglin; Zhang, Shushen
Highlights: SNAD-PBR process with external recycling for energy neutral. Mechanical aeration can be replaced by the SNAD-PBR process. SNAD process can remove nitrogen without adding a carbon source. The reflux system introduced was beneficial to Candidatus Brocadia . Abstract: This study presents a new way to achieve energy neutral wastewater treatment based on a combined nitrification, anammox, and denitrification (SNAD) process and photobioreactor (PBR) configuration with external recycling instead of aeration, and without an additional carbon source, using fixed-film-activated sludge technology (IFAS). The SNAD-PBR process achieved total nitrogen (TN) and phosphorus removal efficiencies of 90 and 100%, respectively. In addition, dissolved oxygen (DO) was controlled in the range 0.4–1.2 mg/L by the introduction of an external recycling system. The presence of microalgae to serve as a carbon source in the SNAD reactor enabled the denitrifiers to survive. When the reflux ratio was 1:3, the lower COD/N protected the activity of the anammox bacteria, not suppressed by the heterotrophic denitrifiers. Microbial community analysis by Illumina MiSeq sequencing revealed that the new environment was more suitable for Candidatus Brocadia when a reflux system was introduced.